Kepemimpinan Kepala Madrasah dalam Mengembangkan Budaya Religius di MTs Walisongo Jatirogo Tuban - Rianto (Idarotuna : Journal of Administrative Science, 2021)
Abstract: The leadership of the madrasah principal is very important to create an organization in the madrasa in changing the behavior of their subordinates so that they can work well towards his duties.A unique and good culture in educational institutions is a school whose human resources and other resources are cultural, civilized, religious, humanist, sensitive and care about the social problems of the community. One model of school culture is to have its own color as unique and in accordance with the goals of national education, namely the formation of student character. The focus of this research: 1) What are the duties and responsibilities of the head of madrasa leadership in developing a religious culture;2) How is the principal's leadership strategy in developing a religious culture; 3) Factors that support and hinder the leadership of the head of the madrasa in developing a religious culture. This research method uses a qualitative approach, the location is at MTs Walisongo Jatirogo Tuban, the data sources are informants, events, locations and documents, the data are primary and secondary, the data collection techniques are observation, interviews and documentation. Analysis of the data with qualitative descriptive analysis, while checking the validity of the data using credibility, dependability, transparency and confirmability.